Dietary Effects of Black-Oat-Rich Polyphenols on Production Traits, Metabolic Profile, Antioxidative Status, and Carcass Quality of Fattening Lambs - Zvonko Antunović; Željka Klir Šalavardić; Boro Mioč; Zvonimir Steiner; Mislav Đidara; Vinko Sičaja; Valentina Pavić; Lovro Mihajlović; Lidija Jakobek; Josip Novoselec (Agriculture)
The study aimed to establish the dietary effects of black oat rich in polyphenols on the production traits, metabolic profile, antioxidant status, and carcass quality of fattening lambs, after weaning. In the BO group, in the feed mixture, common oats replaced the black oat compared to the CO group. The research comprehensively investigated production indicators, blood metabolic profile, antioxidant status, and lamb carcass quality. No significant differences were found in the fattening or slaughter characteristics of lamb carcasses, except for lower pH1 values in BO lamb carcasses. Significant increases in RBC, HCT, and MCV levels as well as TP, ALB, and GLOB concentrations and GPx and SOD activities in the blood of BO lambs were found. The glucose and EOS content as well as the activity of the enzymes ALT and ALP were significantly lower in the blood of the BO group than in the CO group. In the liver, the DPPH activity was significantly higher in the BO lambs compared to the CO lambs. The observed changes in glucose, protein metabolism, and antioxidant status in the blood and tissues of lambs indicate that the use of polyphenol-rich black oats in the diet of lambs under stress conditions is justified.